2017
DOI: 10.3389/fped.2017.00142
|View full text |Cite
|
Sign up to set email alerts
|

Bloodstream Infection Incidence of Different Central Venous Catheters in Neonates: A Descriptive Cohort Study

Abstract: Central venous catheters (CVCs) in neonates are associated with a risk of central line-associated bloodstream infections (CLABSI). Most reports on the incidence of CLABSI in neonates focus on umbilical venous catheters (UVCs) and peripherally inserted central catheters (PICCs). We evaluated the incidence and risk factors for CLABSI in a cohort of neonates with femoral venous catheters (FVCs), UVCs, and PICCs, with a gestational age ≥34 weeks born between January 1, 2006 and June 30, 2013. We included 2,986 neo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
17
3
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 31 publications
5
17
3
4
Order By: Relevance
“…24 Nevertheless, lower rates are present in Europe ranging from 10.6 to 12.3 and United States ranging from 1.8 to 5.2. 24,25 Regarding the causative organisms in this study, gram positive bacteria represented more than half of the causative agents; MRSA 35% and CONS 29% were the most prevalent organisms, this compares to other studies which found CONS 51% and S. aureus 23%. 25 An important fact to note was that DAI rates in the study did not affect patient outcome in terms of mortality; we showed no correlation between patient outcome and CLABSI and VAP rates.…”
Section: Discussioncontrasting
confidence: 68%
See 1 more Smart Citation
“…24 Nevertheless, lower rates are present in Europe ranging from 10.6 to 12.3 and United States ranging from 1.8 to 5.2. 24,25 Regarding the causative organisms in this study, gram positive bacteria represented more than half of the causative agents; MRSA 35% and CONS 29% were the most prevalent organisms, this compares to other studies which found CONS 51% and S. aureus 23%. 25 An important fact to note was that DAI rates in the study did not affect patient outcome in terms of mortality; we showed no correlation between patient outcome and CLABSI and VAP rates.…”
Section: Discussioncontrasting
confidence: 68%
“…24,25 Regarding the causative organisms in this study, gram positive bacteria represented more than half of the causative agents; MRSA 35% and CONS 29% were the most prevalent organisms, this compares to other studies which found CONS 51% and S. aureus 23%. 25 An important fact to note was that DAI rates in the study did not affect patient outcome in terms of mortality; we showed no correlation between patient outcome and CLABSI and VAP rates. The reason for that may be attributed to early diagnosis and strict adherence to medical protocol of treatment and care of nosocomial infection that may have averted an unfavorable outcome.…”
Section: Discussioncontrasting
confidence: 68%
“…Unlike in the adult ICU, implementations of care bundles in pediatric and neonatal intensive care units have had inconsistent outcomes in reducing CLABSIs (Wirtschafter et al, 2010). Additionally, studies in neonates have failed to demonstrate a significant difference in CLABSI risk between catheter types used mostly in the NICU (peripherally inserted, umbilical and femoral) (Dubbink-Verheij et al, 2017). Studies have also shown that it is possible to reduce neonatal CLABSI rates with hospital-based interventions (Bizzarro et al, 2010;Pronovost, 2008).…”
Section: Clabsis In Pediatricsmentioning
confidence: 99%
“…An estimated 21% of babies admitted born at ≥ 34 weeks of gestation and admitted to a NNU receive a CVC, but this proportion rises to 70% for babies born before 32 weeks of gestational age [based on unpublished analysis of the National Neonatal Research Database (NNRD) (Katie Harron, University College London, 2014, personal communication)]. 21 Peripherally inserted central venous catheters (PICCs) are frequently used in NNUs. The PICC is a very narrow tube placed through the skin and into a central vein, using a needle, which is then removed.…”
Section: Introductionmentioning
confidence: 99%